Food intake patterns and factors affecting in preschool children in Bushehr city - Farideh Nazari; Roya Shoara; Faeazeh jahanpour (Iranian South Medical Journal, 2015)
Background: Numerous factors, some obvious and others subtle, determine food intake patterns in children. Likes and dislikes are established in the early years. The purpose of this study is to assess the food consumption pattern and factors affecting in preschool children in bushehr city. Materials and Methods: This is descriptive, analytical study. The total of 191 preschool children (6 years old) was selected at random sampling method. Data were collected by food frequency questionnaire and were analyzed by table of serving sizes food groups for children and adolescents and by SPSS software 16. Results: Frequency Of milk consumption was 41.9% daily, 40.9% weekly, and 12.6% rarely. Frequency Of fish consumption was 1.6% daily, 71.7% weekly, and 16.8% rarely. Frequency Of chicken consumption was 1% daily, 83.4% weekly, and 9.9% rarely. Frequency Of fruit consumption was 69.6% daily, 22% weekly, and 7.3% rarely. There was significant statistical relationship between Frequency consumption Of dairy, salad, fruit , juices, chicken, egg, and fathers ‘job and fathers’ and mothers’ education level.(P<0. 05) Conclusion: It is concluded that situation of food group consumption about dairy, meats, vegetables, cereals is poor but fruit consumption was good in preschool children. Based on results we recommended planning for educational program in relation to Nutrition and food group consumption by media and in school and public centers and health centers.